Dynamics of Ministerial Change and Curriculum Rotation Analyzing Indonesian Education Policy through Literature Study - Nasywaa Hadaina Sabila Husnan; Inayah Dwiwanti Sya'rani; Gibran Sidik Abdussalam; Elis Sofiah (GoResearch - Research & Publishing House, 2025)
This study analyzes the pattern of the relationship between the change of education minister and changes in the national curriculum in Indonesia over the last 10-15 years. The purpose of this study is to analyze the pattern of the relationship between the change of education minister and changes in the national education curriculum in Indonesia, identify the impact of frequent curriculum changes due to political dynamics, and explore other driving factors of curriculum changes based on literature review. Through a qualitative approach with a literature review method, this research examines the